Method for recovering valuable metals in retired ternary lithium battery based on cascade separation of deep eutectic solvent and oxalic acid
By employing a tiered separation method using eutectic solvents and oxalic acid, the problem of efficient separation and recovery of lithium, nickel, cobalt, and manganese elements in retired ternary lithium batteries has been solved. This method enables the preparation of high-purity ternary lithium precursors and the effective enrichment of lithium, and is applicable to the recovery of valuable metals from retired lithium batteries.
Patent Information
- Application Number
- CN202411403752.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
Existing technologies have low leaching rates when recycling lithium, nickel, cobalt, and manganese elements from retired ternary lithium batteries, making it impossible to achieve effective separation and efficient utilization. In particular, the recovery rate of lithium needs to be improved.
The black powder was leached with a eutectic solvent at a liquid-solid ratio at 110–130 °C. Cobalt, nickel, and manganese were then separated by oxalic acid stepwise separation and precipitation. The eutectic solvent after precipitation was recycled, and the lithium filtrate was reused as a eutectic solvent. Finally, lithium was separated by sodium carbonate precipitation to prepare a ternary lithium precursor.
The method achieves efficient separation and recovery of lithium, nickel, cobalt and manganese, and the purity of the prepared ternary lithium precursor reaches more than 99% and the purity of lithium carbonate reaches more than 95%. The method is simple, green and economical, and is suitable for the recovery of valuable metals from retired lithium batteries.
Smart Images

Figure CN119287161A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of recycling of ternary lithium batteries, and in particular to a method for recovering valuable metals in retired ternary lithium batteries based on low eutectic solvent and oxalic acid step separation. Background Art
[0002] The existing ternary lithium battery is widely used in electric vehicles and energy storage due to its high energy density and long cycle life. However, as the use time increases, the battery power will gradually decay, and the scrapped ternary lithium battery needs to be recycled. The existing ternary lithium battery recycling mainly includes three links: pretreatment, recovery of valuable metals and regeneration of materials. The pretreatment link includes: discharge, disassembly and separation, so as to safely and efficiently disassemble the battery into positive electrode materials, negative electrode materials, electrolytes and other valuable components in the battery.
[0003] The recovery of valuable metals includes: recovering valuable metals such as lithium, nickel, cobalt, and manganese contained in various parts of ternary lithium batteries through pyrometallurgical or hydrometallurgical processes. The pyrometallurgical process converts metals into alloys or compounds through high-temperature smelting, while the hydrometallurgical process uses chemical solvents to leach metal ions from battery materials, and then separates and purifies them through extraction, precipitation and other steps.
[0004] The raw materials used for the recovery of valuable metals are mostly black powder. The black powder is obtained by dismantling retired lithium batteries and crushing, screening, pyrolyzing and sorting the positive and negative electrode materials obtained. It is a black powder mainly containing metals such as nickel, cobalt, manganese, lithium and carbon powder.
[0005] For such raw materials, the prior art, such as CN202111241886.5, discloses a method for leaching nickel, cobalt and manganese from waste lithium batteries using a deep eutectic solvent. The method is to mix graphite powder and waste nickel, cobalt and manganese lithium positive electrode materials through ball milling, reduction roasting, stirring and leaching with deionized water, filtering and drying, and then placing the obtained substance in a choline chloride: citric acid mixed solution with a molar ratio of 2:1, leaching at 85°C for 5h, and obtaining a leachate with a solid-liquid ratio of 1:75 (g / ml). The leaching rates of nickel, cobalt and manganese in the leachate are 96.93%, 96.73% and 97.40% respectively. The leaching rates of the three elements need to be improved, and the recycling of lithium elements cannot be achieved at the same time.
[0006] Another example is the method disclosed in CN202310279761.4, which is to roast the positive electrode sheets from waste lithium batteries at 450°C to obtain positive electrode sheet powder, place the obtained powder in a solution of choline chloride: citric acid mixed in a molar ratio of 1:1, add ethanol and water to the solution to obtain a mixed solution, and stir and leach for 2 hours at 90°C; add a precipitant solution (oxalic acid, ethanol, water) to the leachate and hydrothermally react at 180°C for 12 hours to obtain an electrocatalyst containing nickel, cobalt and manganese (specifically NCM oxalate, whose chemical formula is approximately Ni0.33Co0.33 Mn0.33C2O4). This method cannot directly produce metal elements, but can only obtain a catalyst obtained by mixing multiple metal elements, which affects the further use of the recovered metal substances.
[0007] CN202410321425.6 discloses a method for recycling waste ternary lithium batteries to prepare ternary precursors. A low eutectic solvent composed of tetrabutylammonium chloride, thenoyl trichloroacetone, benzoyl trichloroacetone, ethanol and citric acid (oxalic acid or tartaric acid) is used to recycle waste ternary lithium battery positive electrode materials. At 90 ° C, the liquid-solid ratio is 30ml / g, and the leaching is 120min. The leaching rate of Li is 93.31%, the leaching rate of Ni is 97.69%, the leaching rate of Co is 98.12%, and the leaching rate of Mn is 99.22%. Although efficient leaching of lithium, cobalt, nickel and manganese can be achieved under relatively mild conditions, the composition of the low eutectic solvent species is relatively large, which is not conducive to the reuse of valuable metals after recovery. The leaching rate of lithium needs to be improved.
[0008] CN202311193870.0 relates to a method for recovering and regenerating waste lithium-ion battery positive electrode materials using deep eutectic solvents. The method directly places the waste ternary lithium battery in a mixed solution of guanidine hydrochloride and formic acid with a molar ratio of 1:4 and a liquid-to-solid ratio of 1 / 50 g / g, and stirs at 140°C for 80 minutes. The leaching rates of lithium, nickel, cobalt and manganese in the leachate are 97.79%, 94.14%, 95.79% and 93.75%, respectively. The leaching rates of the four metals need to be improved under high temperature and high liquid-to-solid ratio conditions.
[0009] The information disclosed in the background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0010] The present application provides a method for recovering valuable metals in retired ternary lithium batteries based on low eutectic solvent and oxalic acid cascade separation. The method can simultaneously collect lithium, nickel, cobalt and manganese in the ternary lithium battery in the form of compounds, thereby achieving comprehensive recycling.
[0011] The present application provides a method for recovering valuable metals in retired ternary lithium batteries based on a deep eutectic solvent and oxalic acid stepwise separation, comprising the following steps:
[0012] 1) the low eutectic solvent and the black powder are stirred and leached at 110-130° C. for 3-4 hours at a liquid-to-solid ratio of 5-50:1 (ml:g) to obtain a leachate;
[0013] 2) measuring the contents of lithium, cobalt, nickel and manganese in the leachate according to ICP, adding oxalic acid in excess of the required amount according to the contents of lithium, cobalt, nickel and manganese, stirring and standing, and then centrifuging to obtain a precipitate mixture of nickel oxalate precipitate, cobalt oxalate precipitate, manganese oxalate precipitate and lithium filtrate;
[0014] 3) using the lithium filtrate obtained in each step as a low eutectic solvent, repeating steps 1 to 2) at least 3 times, and then adding sodium carbonate and centrifuging to obtain a lithium carbonate precipitate after rotary evaporation of the final lithium filtrate;
[0015] 4) combining the precipitation mixtures obtained in each step, dissolving the precipitation mixture with sulfuric acid, measuring the concentrations of nickel, cobalt and manganese in the mixed solution, adding nickel sulfate, cobalt sulfate or manganese sulfate solution, adjusting the pH, and adding ammonia water to obtain a ternary lithium precursor (Ni0.5Co0.2Mn0.3)(OH)2;
[0016] The low eutectic solvent is prepared by mixing choline chloride and citric acid in a molar ratio of 2:1-0.5 and adding 35-45% water of the obtained mixture.
[0017] The black powder preparation method comprises the following steps:
[0018] The waste lithium battery materials were placed in a 0.1 mol / L sodium chloride solution and soaked for 48 hours for discharge treatment. The waste lithium battery that was completely discharged was cut with diagonal pliers under a fume hood, and the positive electrode material was manually separated from the metal shell and the organic film, and cut into small pieces using a cutter. The positive electrode material was taken out and roasted at 700°C for 2 hours to remove the organic material. The calcined material was immersed in a NaOH solution to separate the aluminum foil from the cathode, and the obtained black material had a particle size of 5 to 15 μm after grinding. The obtained black substance was dried in an oven at 70°C to obtain a black substance containing nickel, cobalt, and manganese lithium oxide.
[0019] Preferably, after completing steps 1 to 2) for the first time, the obtained precipitation mixture and lithium filtrate are subjected to the first leaching, in which: the leaching rate of lithium is 91.37 to 99.45%, the leaching rate of nickel is 95.21 to 99.21%, the leaching rate of manganese is 93.79 to 99.79%, and the leaching rate of cobalt is 94.24 to 99.24%.
[0020] Preferably, the mixture is allowed to stand for 3 to 4 hours after the oxalic acid is added.
[0021] Preferably, the obtained nickel oxalate, cobalt oxalate and manganese oxalate precipitate mixture is washed twice with water and ethanol and then dried for standby use.
[0022] Preferably, the lithium filtrate is used as a low eutectic solvent after removing water by rotary evaporation.
[0023] Preferably, after completing steps 1 to 2) for the second time, the obtained precipitation mixture and lithium filtrate are subjected to the second leaching, and in the second leaching: the leaching rate of lithium is 90.42 to 97.42%, the leaching rate of nickel is 91.96 to 98.96%, the leaching rate of manganese is 91.64 to 99.64%, and the leaching rate of cobalt is 92.32 to 99.32%.
[0024] Preferably, the nickel sulfate, cobalt sulfate or manganese sulfate solution is supplemented at a molar ratio of nickel, cobalt and manganese of 5:2:3.
[0025] Preferably, the pH value is adjusted to 12 using NaOH.
[0026] Preferably, the deep eutectic solvent is prepared by mixing choline chloride and citric acid in a molar ratio of 2:1 and adding 35% water by volume of the resulting mixture.
[0027] Preferably, after completing steps 1 to 2) for the third time, the obtained precipitation mixture and lithium filtrate are leached for the third time, and in the third leaching: the leaching rate of lithium is 91.42 to 95.42%, the leaching rate of nickel is 91.96 to 95.96%, the leaching rate of manganese is 90.64 to 95.64%, and the leaching rate of cobalt is 89.32 to 95.32%.
[0028] Specifically, the method comprises the following steps:
[0029] (1) Deep eutectic solvent leaching
[0030] Weigh a certain amount of choline chloride and citric acid in a beaker, stir at 70°C for 10 min to prepare a low eutectic solvent. Weigh a certain amount of black powder into a round-bottom flask, add the corresponding volume of low eutectic solvent at a liquid-to-solid ratio (ml / g) of 10:1, and stir and leach at 120°C for 4 h in an oil bath.
[0031] (2) The contents of lithium, cobalt, nickel and manganese in the filtrate were measured using ICP and the leaching rate was calculated.
[0032] (3) Add an equal volume of deionized water.
[0033] (4) According to the stoichiometric ratio of the chemical equation, a slightly excess amount of oxalic acid is added to precipitate nickel oxalate, cobalt oxalate and manganese oxalate (lithium is retained in the low eutectic solvent).
[0034] (5) Rotary evaporation of part of the water in the eutectic solvent.
[0035] (6) A certain amount of black powder and the recovered low eutectic solvent were weighed and added into a round-bottom flask, and then stirred and leached at 120° C. for 4 h in an oil bath.
[0036] (7) The contents of lithium, cobalt, nickel and manganese in the filtrate were measured using ICP and the leaching rate was calculated.
[0037] (8) After multiple cycles of use, the lithium in the deep eutectic solvent is precipitated with sodium carbonate.
[0038] The beneficial effects of this application include:
[0039] 1) The present application provides a method for recovering valuable metals in retired ternary lithium batteries based on low eutectic solvent and oxalic acid step separation. The low eutectic solvent is first used for leaching, and then the cobalt, nickel and manganese are separated by oxalic acid step precipitation. The precipitated low eutectic solvent is continuously used for leaching of black powder. After several cycles of use, the lithium is separated by sodium carbonate precipitation. The low eutectic solvent is obtained by compounding choline chloride and citric acid. The low eutectic solvent is simple to prepare, environmentally friendly, and recyclable. It still has a good leaching effect when reused, and has great application prospects for recovering valuable metals in waste lithium batteries.
[0040] 2) The present application provides a method for recovering valuable metals from retired ternary lithium batteries based on low eutectic solvent and oxalic acid step separation. The obtained oxalic acid precipitate is used for the subsequent preparation of ternary lithium precursors; the low eutectic solvent is further used for leaching black powder, and the lithium is precipitated with sodium carbonate after several cycles. This method is simple to operate, the raw materials are easily available, it is green and economical, the reaction conditions are mild and the stability is high. It has broad application prospects and is particularly suitable for recovering valuable metals from retired lithium batteries.
[0041] 3) The method for recovering valuable metals in retired ternary lithium batteries based on low eutectic solvent and oxalic acid step separation provided in this application can achieve effective separation and recycling of the three elements. This method can effectively recover the valuable metals in the leachate. Under the optimal conditions, the purity of the ternary lithium precursor prepared by the cobalt, nickel and manganese obtained by this method can reach more than 99%, and the purity of the obtained lithium carbonate can reach more than 95%, realizing closed-loop recycling.
[0042] 4) The present application provides a method for recovering valuable metals in retired ternary lithium batteries based on low eutectic solvent and oxalic acid step separation. The method can be used to collect lithium, nickel, cobalt and manganese in black powder in the form of compounds. The effective recycling of valuable metals in retired ternary lithium batteries is achieved. In addition, the method uses the lithium filtrate from the previous time as the low eutectic solvent for the next time, which not only reduces the amount of low eutectic solvent used, but also effectively enriches the lithium element in the black powder. In addition, the method will not affect the subsequent recovery of lithium elements in the black powder due to the excessively high lithium content.
[0043] 5) The present application provides a method for recovering valuable metals in retired ternary lithium batteries based on low eutectic solvent and oxalic acid step separation. The organic acid used in this method is citric acid, which has a strong reducing property. The ionization energy of citric acid is theoretically calculated to be lower than 950 kJ / mol. Therefore, it exhibits a good hydrogen bond donor effect in this method, thereby effectively improving the leaching rate of each element in the leaching process. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 A schematic flow chart of a method for recovering valuable metals in retired ternary lithium batteries based on deep eutectic solvent and oxalic acid step separation in at least one embodiment provided in the present application; DETAILED DESCRIPTION
[0045] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, but the present invention is not limited in any way. Any changes or improvements made based on the teachings of the present invention fall within the protection scope of the present invention.
[0046] Example
[0047] Unless otherwise specified, the materials and instruments used in the following examples were obtained from commercial channels; the detection methods used were all existing methods unless otherwise specified.
[0048] Embodiment 1:
[0049] Preparation of black powder: Soak the waste lithium battery material in a 0.1 mol / L sodium chloride solution for 48 hours for discharge treatment. Use diagonal pliers to cut open the fully discharged waste lithium battery under a fume hood. Manually separate the positive electrode material from the metal shell and the organic film, and cut it into small pieces using a cutter. Take out the positive electrode material and roast it at 700°C for 2 hours to remove the organic material. Immerse the calcined material in a NaOH solution to separate the aluminum foil from the cathode. After grinding the obtained material, a black substance with a particle size of 5 to 15 μm is obtained. The obtained black substance is dried in an oven at 70°C to obtain a black powder containing nickel, cobalt, manganese lithium oxide.
[0050] Weigh 0.2 mol (28 g) of choline chloride and 0.1 mol (19.2 g) of citric acid respectively and add them to a 150 ml beaker, stir at 70 °C until a clear and transparent solution is formed, and then add 35% of the volume of water. Weigh 4.80 g of black powder, add 48 ml of low eutectic solvent at a liquid-solid ratio (ml / g) of 10:1, use an oil bath to stir and leach at 120 °C for 4 hours, and after the reaction is completed, filter to obtain 0.23 g of residue and filtrate.
[0051] Add the filtrate to a 100ml volumetric flask and make up to volume. Take 1ml of the above filtrate and add it to a 100ml volumetric flask. Add 2ml of nitric acid and make up to volume for testing. Finally, use ICP to measure the content of lithium, cobalt, nickel and manganese in the filtrate. According to the measurement results, the leaching rate of valuable metals in the black powder after the first leaching is as follows: lithium: 91.37%; nickel: 98.21%; manganese: 96.79%; cobalt: 97.24%.
[0052] Subsequently, an equal volume of water and 4.6 g of oxalic acid were added, and the mixture was allowed to stand for 3 hours before centrifugation to obtain a mixture of nickel oxalate, cobalt oxalate and manganese oxalate precipitations, which was washed twice with water and ethanol and then dried. After weighing, 6.65 g of precipitate was obtained. The filtrate was used to measure the contents of lithium, cobalt, nickel and manganese using ICP. According to the measurement results, it was calculated that 96% of the lithium was retained in the solution, and more than 99% of the nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0053] Subsequently, the filtrate was rotary evaporated to remove part of the water and transferred to a round-bottom flask. 4.80 g of black powder was weighed and added to the round-bottom flask. 48 ml of the filtrate obtained after the first leaching was added as a low eutectic solvent at a liquid-to-solid ratio (ml / g) of 10:1. The mixture was stirred and leached in an oil bath at 120°C for 4 h. After the reaction was completed, 0.32 g of residue and filtrate were obtained by suction filtration.
[0054] The filtrate was added to a 100 ml volumetric flask and fixed to volume. 1 ml of the filtrate was added to a 100 ml volumetric flask, and 2 ml of nitric acid was added to fix to volume for testing. Finally, the contents of lithium, cobalt, nickel and manganese in the filtrate were measured by ICP. According to the measurement results, the leaching rates of valuable metals in the black powder during the second leaching process were as follows: lithium: 88.42%; nickel: 92.96%; manganese: 91.64%; cobalt: 94.32%.
[0055] Subsequently, an equal volume of water and 4.30 g of oxalic acid were added, and after standing for 3 hours, a mixture of nickel oxalate, cobalt oxalate and manganese oxalate was obtained by centrifugation. After washing twice with water and ethanol and drying, 5.96 g of precipitate was obtained by weighing. According to the measurement results, 94% of lithium was retained in the solution, and more than 96% of nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0056] Subsequently, most of the water was evaporated off, 5.00 g of sodium carbonate was added, and the mixture was centrifuged and dried to obtain 3.90 g of lithium carbonate precipitate.
[0057] Weigh part of the precipitated mixture of nickel oxalate, cobalt oxalate and manganese oxalate and dissolve it with sulfuric acid, measure the concentrations of nickel, cobalt and manganese, add corresponding nickel sulfate, cobalt sulfate or manganese sulfate to make the molar ratio of nickel, cobalt and manganese in the solution be 5:2:3, finally adjust the pH of the solution to 12 with NaOH, add a small amount of ammonia water to obtain (Ni0.5Co0.2Mn0.3)(OH)2 precipitate, which is the ternary lithium precursor.
[0058] Embodiment 2:
[0059] Preparation of black powder: Same as Example 1.
[0060] Weigh 0.05 mol (7.00 g) of choline chloride and 0.025 mol (4.80 g) of citric acid respectively and add them to a 50 ml beaker, stir at 70 °C until a clear and transparent solution is formed, and then add 35% of the volume of the solution of water. Weigh 0.40 g of black powder, add 12 ml of low eutectic solvent at a liquid-solid ratio (ml / g) of 30:1, use an oil bath to stir and leach at 120 °C for 4 hours, and after the reaction is completed, filter to obtain 0.00 g of filter residue and filtrate.
[0061] Add the filtrate to a 100ml volumetric flask and make up to volume. Take 1ml of the above filtrate and add it to a 100ml volumetric flask. Add 2ml of nitric acid and make up to volume for testing. Finally, use ICP to measure the content of lithium, cobalt, nickel and manganese in the filtrate. According to the measurement results, after the first leaching, the leaching rate of valuable metals in the black powder is as follows: lithium: 99.37%; nickel: 99.21%; manganese: 99.79%; cobalt: 99.24%.
[0062] Subsequently, an equal volume (100 ml) of water was added, and 0.35 g of oxalic acid was added. After standing for 3 h, a mixture of nickel oxalate, cobalt oxalate and manganese oxalate was obtained by centrifugation. The mixture was washed twice with water and ethanol and then dried. After weighing, 0.52 g of precipitate was obtained.
[0063] The contents of lithium, cobalt, nickel and manganese in the filtrate were measured by ICP. According to the measurement results, 98% of lithium was retained in the solution, and more than 99% of nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0064] Subsequently, part of the water in the filtrate was evaporated and transferred to a round-bottom flask, 0.40 g of black powder was weighed and added to the round-bottom flask, 12 ml of the filtrate obtained after the first leaching was added as a low eutectic solvent at a liquid-to-solid ratio (ml / g) of 30:1, and the mixture was stirred and leached at 120°C for 4 h in an oil bath. After the reaction was completed, 0.05 g of residue and filtrate were obtained by suction filtration.
[0065] Add the filtrate to a 100ml volumetric flask and make up to volume. Take 1ml of the above filtrate and add it to a 100ml volumetric flask. Add 2ml of nitric acid and make up to volume for testing.
[0066] Finally, ICP was used to measure the contents of lithium, cobalt, nickel and manganese in the filtrate. According to the measurement results, the leaching rates of valuable metals in the black powder during the second leaching process were as follows: lithium: 95.42%; nickel: 95.96%; manganese: 95.64%; cobalt: 95.32%.
[0067] Subsequently, an equal volume of water and 0.30 g of oxalic acid were added. After standing for 3 hours, the mixture was centrifuged to obtain a precipitate mixture of nickel oxalate, cobalt oxalate and manganese oxalate. The mixture was washed twice with water and ethanol and then dried. 0.51 g of precipitate was weighed and calculated based on the measurement results. 96% of the lithium was retained in the solution, and more than 97% of the nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0068] Subsequently, part of the water was evaporated and transferred to a round-bottom flask, 0.40g of black powder was weighed and added to the round-bottom flask, 12ml of the filtrate obtained after the second leaching was added as a low eutectic solvent at a liquid-to-solid ratio (ml / g) of 30:1, and an oil bath was used to stir and leach for 4h at 120℃. After the reaction was completed, 0.08g of filter residue and filtrate were obtained by suction filtration. The filtrate was added to a 100ml volumetric flask to make up the volume, 1ml of the above filtrate was added to a 100ml volumetric flask, 2ml of nitric acid was added, and the volume was made up for testing.
[0069] Finally, ICP was used to measure the contents of lithium, cobalt, nickel and manganese in the filtrate. According to the measurement results, the leaching rates of valuable metals in the black powder during the third leaching process were as follows: lithium: 90.42%; nickel: 91.96%; manganese: 91.64%; cobalt: 92.32%.
[0070] Subsequently, an equal volume of water and 0.30 g of oxalic acid were added. After standing for 3 hours, the mixture was centrifuged to obtain a precipitate mixture of nickel oxalate, cobalt oxalate and manganese oxalate. The mixture was washed twice with water and ethanol and then dried. 0.49 g of precipitate was weighed and calculated based on the measurement results. 94% of the lithium was retained in the solution, and more than 95% of the nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0071] Subsequently, most of the water was evaporated off and 0.65 g of sodium carbonate was added, and 0.52 g of lithium carbonate precipitate was obtained after centrifugal separation.
[0072] After dissolving the precipitated mixture of nickel oxalate, cobalt oxalate and manganese oxalate with sulfuric acid, the concentrations of nickel, cobalt and manganese were measured, and the corresponding nickel sulfate, cobalt sulfate or manganese sulfate were added to make the molar ratio of nickel, cobalt and manganese in the solution be 5:2:3. Finally, the pH of the solution was adjusted to 12 with NaOH, and a small amount of ammonia water was added to obtain (Ni0.5Co0.2Mn0.3)(OH)2 precipitate, which is the ternary lithium precursor.
[0073] Embodiment 3:
[0074] Preparation of black powder: Same as Example 1.
[0075] Weigh 0.05 mol (7.00 g) of choline chloride and 0.025 mol (4.80 g) of citric acid respectively and add them to a 50 ml beaker, stir at 70 °C until a clear and transparent solution is formed, and then add 35% of the volume of the solution of water. Weigh 0.24 g of black powder, add 12 ml of low eutectic solvent at a liquid-solid ratio (ml / g) of 50:1, use an oil bath to stir and leach at 120 °C for 4 hours, and after the reaction is completed, filter to obtain 0.00 g of filter residue and filtrate.
[0076] Add the filtrate to a 100ml volumetric flask and make up to volume. Take 1ml of the above filtrate and add it to a 100ml volumetric flask. Add 2ml of nitric acid and make up to volume for testing. Finally, use ICP to measure the content of lithium, cobalt, nickel and manganese in the filtrate. According to the measurement results, the leaching rate of valuable metals in black powder is as follows: lithium: 99.45%; nickel: 99.78%; manganese: 99.87%; cobalt: 99.63%.
[0077] Subsequently, an equal volume of water and 0.16 g of oxalic acid were added, and after standing for 3 hours, a mixture of nickel oxalate, cobalt oxalate and manganese oxalate precipitation was obtained by centrifugation. The mixture was washed twice with water and ethanol and then dried. After weighing, 0.31 g of precipitation was obtained.
[0078] The remaining solution was measured for lithium, cobalt, nickel and manganese contents using ICP. Based on the measurement results, it was calculated that 98% of the lithium remained in the solution, and more than 99% of the nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0079] Subsequently, part of the water was rotary evaporated and transferred to a round-bottom flask, 0.24 g of black powder was weighed and added to the round-bottom flask, 12 ml of the filtrate obtained after the first leaching was added as a low eutectic solvent at a liquid-to-solid ratio (ml / g) of 50:1, and the mixture was stirred and leached at 120°C for 4 h in an oil bath. After the reaction was completed, 0.02 g of residue and filtrate were obtained by suction filtration.
[0080] The filtrate was added to a 100 ml volumetric flask and fixed to volume. 1 ml of the filtrate was added to a 100 ml volumetric flask, and 2 ml of nitric acid was added to fix to volume for testing. Finally, the contents of lithium, cobalt, nickel and manganese in the filtrate were measured by ICP. According to the measurement results, the leaching rates of valuable metals in the black powder during the second leaching process were as follows: lithium: 97.42%; nickel: 98.96%; manganese: 99.64%; cobalt: 99.32%.
[0081] Subsequently, an equal volume of water and 0.16 g of oxalic acid were added. After standing for 3 hours, the mixture was centrifuged to obtain a precipitate mixture of nickel oxalate, cobalt oxalate and manganese oxalate. The mixture was washed twice with water and ethanol and then dried. 0.30 g of precipitate was weighed and calculated based on the measurement results. 96% of the lithium was retained in the solution, and more than 97% of the nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0082] Subsequently, part of the water was evaporated and transferred to a round-bottom flask, 0.24 g of black powder was weighed and added to the round-bottom flask, 12 ml of the filtrate obtained after the second leaching was added as a low eutectic solvent at a liquid-solid ratio (ml / g) of 50:1, and an oil bath was used to stir and leach for 4 h at 120 ° C. After the reaction was completed, 0.04 g of filter residue and filtrate were obtained by suction filtration. The filtrate was added to a 100 ml volumetric flask to make up the volume, 1 ml of the above filtrate was added to a 100 ml volumetric flask, 2 ml of nitric acid was added, and the volume was made up for testing.
[0083] Finally, the contents of lithium, cobalt, nickel and manganese in the filtrate were measured by ICP. According to the measurement results, the leaching rates of valuable metals in the black powder during the third leaching process were as follows: lithium: 90.42%; nickel: 91.96%; manganese: 91.64%; cobalt: 92.32%. Subsequently, an equal volume of water and 0.14g of oxalic acid were added, and after standing for 3 hours, a mixture of nickel oxalate, cobalt oxalate and manganese oxalate precipitation was obtained by centrifugation. After washing twice with water and ethanol and drying, 0.28g of precipitation was obtained by weighing. According to the measurement results, 94% of lithium was retained in the solution, and more than 95% of nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0084] Subsequently, part of the water was evaporated and transferred to a round-bottom flask, 0.24 g of black powder was weighed and added to the round-bottom flask, 12 ml of the filtrate obtained after the third leaching was added as a low eutectic solvent at a liquid-to-solid ratio (ml / g) of 50:1, and the mixture was stirred and leached at 120°C for 4 h in an oil bath. After the reaction was completed, 0.02 g of residue and filtrate were obtained by suction filtration.
[0085] The filtrate was added to a 100 ml volumetric flask and fixed to volume. 1 ml of the filtrate was added to a 100 ml volumetric flask, and 2 ml of nitric acid was added to fix to volume for testing. Finally, the contents of lithium, cobalt, nickel and manganese in the filtrate were measured by ICP. According to the measurement results, the leaching rates of valuable metals in the black powder during the fourth leaching process were as follows: lithium: 88.68%; nickel: 90.41%; manganese: 89.76%; cobalt: 90.66%.
[0086] Subsequently, an equal volume of water and 0.12 g of oxalic acid were added. After standing for 3 hours, the mixture was centrifuged to obtain a precipitate mixture of nickel oxalate, cobalt oxalate and manganese oxalate. The mixture was washed twice with water and ethanol and then dried. 0.25 g of precipitate was weighed and calculated based on the measurement results. 90% of the lithium was retained in the solution, and more than 90% of the nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0087] After most of the water was evaporated, 0.52g of sodium carbonate was added, and 0.41g of lithium carbonate precipitate was obtained after centrifugal separation. The precipitate mixture of nickel oxalate, cobalt oxalate and manganese oxalate was dissolved with sulfuric acid, and the concentrations of nickel, cobalt and manganese were measured. The corresponding nickel sulfate, cobalt sulfate or manganese sulfate was added to make the molar ratio of nickel, cobalt and manganese in the solution 5:2:3. Finally, the pH of the solution was adjusted to 12 with NaOH, and a small amount of ammonia water was added to obtain (Ni0.5Co0.2Mn0.3)(OH)2 precipitate, which is the ternary lithium precursor.
[0088] Example 4
[0089] The difference from Example 1 is that the low eutectic solvent and the black powder are in a liquid-to-solid ratio of 5:1, and the leaching solution is obtained after stirring and leaching for 3 hours at 130°C; the low eutectic solvent is choline chloride: citric acid mixed in a molar ratio of 2:1 and 35% of the volume of the mixture is added with water.
[0090] Weigh 0.1 mol (14 g) of choline chloride and 0.05 mol (9.6 g) of citric acid respectively and add them to a 50 ml beaker, stir at 70 °C until a clear and transparent melt is formed, and then add 35% of the volume of the melt of water. Weigh 4.80 g of black powder, add 24 ml of low eutectic flux at a liquid-solid ratio (ml / g) of 5:1, use an oil bath to stir and leach at 130 °C for 4 hours, and after the reaction is completed, filter to obtain 0.20 g of filter residue and filtrate.
[0091] Add the filtrate to a 100ml volumetric flask and make up to volume. Take 1ml of the above filtrate and add it to a 100ml volumetric flask. Add 2ml of nitric acid and make up to volume for testing. Finally, use ICP to measure the content of lithium, cobalt, nickel and manganese in the filtrate. According to the measurement results, the leaching rate of valuable metals after the first leaching in the black powder is as follows: lithium: 92.96%; nickel: 97.54%; manganese: 94.15%; cobalt: 95.65%.
[0092] Subsequently, an equal volume of water and 4.60 g of oxalic acid were added, and the mixture was allowed to stand for 3 hours and then centrifuged to obtain a mixture of nickel oxalate, cobalt oxalate and manganese oxalate precipitations, which was washed twice with water and ethanol and then dried. After weighing, 6.68 g of precipitate was obtained. The filtrate was used to measure the contents of lithium, cobalt, nickel and manganese by ICP. According to the measurement results, it was calculated that 97% of the lithium was retained in the melt, and more than 98% of the nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0093] Subsequently, the filtrate was transferred to a round-bottom flask after removing part of the water by rotary evaporation. 4.8g of black powder was weighed and added to the round-bottom flask. 24ml of the filtrate obtained from the first leaching was added as a low eutectic flux at a liquid-to-solid ratio (ml / g) of 5:1. The leaching was stirred in an oil bath at 130°C for 3h. After the reaction was completed, 0.29g of filter residue and filtrate were obtained by suction filtration. The filtrate was added to a 100ml volumetric flask and the volume was fixed. 1ml of the above filtrate was added to a 100ml volumetric flask, and 2ml of nitric acid was added to the volume for testing. Finally, the content of lithium, cobalt, nickel and manganese in the filtrate was measured by ICP. According to the measurement results, the leaching rate of valuable metals in the second leaching black powder was calculated as follows: lithium: 89.63%; nickel: 94.96%; manganese: 92.33%; cobalt: 91.32%.
[0094] Subsequently, an equal volume of water and 4.65 g of oxalic acid were added, and after standing for 3 hours, a mixture of nickel oxalate, cobalt oxalate and manganese oxalate was obtained by centrifugation. After washing twice with water and ethanol and drying, 6.00 g of precipitate was obtained by weighing. According to the measurement results, 95% of lithium was retained in the melt, and more than 96% of nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0095] Subsequently, most of the water was evaporated off, 5.00 g of sodium carbonate was added, and the mixture was centrifuged and dried to obtain 3.91 g of lithium carbonate precipitate.
[0096] Weigh part of the precipitated mixture of nickel oxalate, cobalt oxalate and manganese oxalate and dissolve it with sulfuric acid, measure the concentrations of nickel, cobalt and manganese, add corresponding nickel sulfate, cobalt sulfate or manganese sulfate to make the molar ratio of nickel, cobalt and manganese in the melt be 5:2:3, finally adjust the pH of the melt to 12 with NaOH, add a small amount of ammonia water to obtain (Ni0.5Co0.2Mn0.3)(OH)2 precipitate, which is the ternary lithium precursor.
[0097] Example 5
[0098] The difference from Example 1 is that: the leaching solution is obtained after stirring and leaching at 110° C. for 4 hours; and steps 1 to 2) are repeated 4 times.
[0099] The deep eutectic solvent is prepared by mixing choline chloride and citric acid in a molar ratio of 2:0.5 and adding 45% of the volume of water to the resulting mixture.
[0100] Weigh 0.2 mol (28 g) of choline chloride and 0.05 mol (4.8 g) of citric acid respectively and add them to a 50 ml beaker, stir at 70 °C until a clear and transparent melt is formed, and then add 35% of the volume of the melt of water. Weigh 2.40 g of black powder, add 24 ml of low eutectic flux at a liquid-solid ratio (ml / g) of 10:1, use an oil bath to stir and leach at 110 °C for 4 hours, and after the reaction is completed, filter to obtain 0.92 g of filter residue and filtrate.
[0101] The filtrate was added to a 100 ml volumetric flask and fixed to volume. 1 ml of the filtrate was added to a 100 ml volumetric flask and 2 ml of nitric acid was added to fix to volume for testing. Finally, the contents of lithium, cobalt, nickel and manganese in the filtrate were measured using ICP.
[0102] Subsequently, an equal volume of water and 1.87 g of oxalic acid were added, and the mixture was allowed to stand for 3 hours before centrifugation to obtain a mixture of nickel oxalate, cobalt oxalate and manganese oxalate precipitations, which was washed twice with water and ethanol and then dried. After weighing, 3.64 g of precipitate was obtained. The filtrate was used to measure the contents of lithium, cobalt, nickel and manganese by ICP. According to the measurement results, it was calculated that 97% of the lithium was retained in the melt, and more than 94% of the nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0103] Subsequently, the filtrate was transferred to a round-bottom flask after removing part of the water by rotary evaporation. 2.40g of black powder was weighed and added to the round-bottom flask. 24ml of the filtrate obtained from the first leaching was added as a low eutectic flux at a liquid-to-solid ratio (ml / g) of 10:1. The leaching was stirred in an oil bath at 110°C for 4h. After the reaction was completed, 0.98g of filter residue and filtrate were obtained by suction filtration. The filtrate was added to a 100ml volumetric flask to make up the volume. 1ml of the above filtrate was added to a 100ml volumetric flask, and 2ml of nitric acid was added to make up the volume for testing.
[0104] Subsequently, an equal volume of water and 1.87 g of oxalic acid were added, and after standing for 3 hours, a mixture of nickel oxalate, cobalt oxalate and manganese oxalate was obtained by centrifugation. After washing twice with water and ethanol and drying, 3.59 g of precipitate was obtained by weighing. According to the measurement results, 96% of lithium was retained in the melt, and more than 93% of nickel, cobalt and manganese were recovered by oxalic acid precipitation.
[0105] Subsequently, most of the water was evaporated off, 4.00 g of sodium carbonate was added, and the mixture was centrifuged and dried to obtain 2.79 g of lithium carbonate precipitate.
[0106] Weigh part of the precipitated mixture of nickel oxalate, cobalt oxalate and manganese oxalate and dissolve it with sulfuric acid, measure the concentrations of nickel, cobalt and manganese, add corresponding nickel sulfate, cobalt sulfate or manganese sulfate to make the molar ratio of nickel, cobalt and manganese in the melt be 5:2:3, finally adjust the pH of the melt to 12 with NaOH, add a small amount of ammonia water to obtain (Ni0.5Co0.2Mn0.3)(OH)2 precipitate, which is the ternary lithium precursor.
[0107] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for recovering valuable metals from retired ternary lithium batteries based on deep eutectic solvent and oxalic acid step separation, characterized in that: The following steps are involved: 1) the low eutectic solvent and the black powder are stirred and leached at 110-130° C. for 3-4 hours at a liquid-to-solid ratio of 5-50:1 (ml:g) to obtain a leachate; 2) measuring the contents of lithium, cobalt, nickel and manganese in the leachate according to ICP, adding oxalic acid in excess of the required amount according to the contents of lithium, cobalt, nickel and manganese, stirring and standing, and then centrifuging to obtain a precipitate mixture of nickel oxalate precipitate, cobalt oxalate precipitate, manganese oxalate precipitate and lithium filtrate; 3) using the lithium filtrate obtained in each step as a low eutectic solvent, repeating steps 1 to 2) at least 3 times, and then adding sodium carbonate and centrifuging to obtain a lithium carbonate precipitate after rotary evaporation of the final lithium filtrate; 4) combining the precipitation mixtures obtained in each step, dissolving the precipitation mixture with sulfuric acid, measuring the concentrations of nickel, cobalt and manganese in the mixed solution, adding nickel sulfate, cobalt sulfate or manganese sulfate solution, adjusting the pH value, and adding ammonia water to obtain a ternary lithium precursor (Ni 0.5 Co 0.2 Mn 0.3 )(OH)2; The low eutectic solvent is prepared by mixing choline chloride and citric acid in a molar ratio of 2:1-0.5 and adding 35-45% water of the obtained mixture.
2. The method for recovering valuable metals in retired ternary lithium batteries based on deep eutectic solvent and oxalic acid step separation according to claim 1, characterized in that: After completing steps 1 to 2) for the first time, the obtained precipitation mixture and lithium filtrate are used for the first leaching. In the first leaching, the leaching rate of lithium is 91.37 to 99.45%, the leaching rate of nickel is 95.21 to 99.21%, the leaching rate of manganese is 93.79 to 99.79%, and the leaching rate of cobalt is 94.24 to 99.24%.
3. The method for recovering valuable metals in retired ternary lithium batteries based on deep eutectic solvent and oxalic acid step separation according to claim 1, characterized in that: After adding oxalic acid, let it stand for 3 to 4 hours.
4. The method for recovering valuable metals in retired ternary lithium batteries based on deep eutectic solvent and oxalic acid step separation according to claim 1, characterized in that: The obtained nickel oxalate, cobalt oxalate and manganese oxalate precipitate mixture is washed twice with water and ethanol and then dried for later use.
5. The method for recovering valuable metals in retired ternary lithium batteries based on deep eutectic solvent and oxalic acid step separation according to claim 1, characterized in that: The lithium filtrate was rotary evaporated to remove water and used as a deep eutectic solvent.
6. The method for recovering valuable metals in retired ternary lithium batteries based on deep eutectic solvent and oxalic acid step separation according to claim 1, characterized in that: After completing steps 1 to 2) for the second time, the obtained precipitation mixture and lithium filtrate are leached for the second time. In the second leaching, the leaching rate of lithium is 90.42 to 97.42%, the leaching rate of nickel is 91.96 to 98.96%, the leaching rate of manganese is 91.64 to 99.64%, and the leaching rate of cobalt is 92.32 to 99.32%.
7. The method for recovering valuable metals in retired ternary lithium batteries based on deep eutectic solvent and oxalic acid step separation according to claim 1, characterized in that: Nickel sulfate, cobalt sulfate or manganese sulfate solution is added according to the molar ratio of nickel, cobalt and manganese of 5:2:
3.
8. The method for recovering valuable metals in retired ternary lithium batteries based on deep eutectic solvent and oxalic acid step separation according to claim 1, characterized in that: The pH value was adjusted to 12 using NaOH.
9. The method for recovering valuable metals in retired ternary lithium batteries based on deep eutectic solvent and oxalic acid step separation according to claim 1, characterized in that: The deep eutectic solvent is prepared by mixing choline chloride and citric acid in a molar ratio of 2:1 and adding 35% water of the resulting mixture.
10. The method for recovering valuable metals in retired ternary lithium batteries based on deep eutectic solvent and oxalic acid step separation according to claim 1, characterized in that: After completing steps 1 to 2) for the third time, the obtained precipitation mixture and lithium filtrate are leached for the third time. In the third leaching, the leaching rate of lithium is 88.42 to 95.42%, the leaching rate of nickel is 91.96 to 95.96%, the leaching rate of manganese is 90.64 to 95.64%, and the leaching rate of cobalt is 89.32 to 95.32%.
Citation Information
Patent Citations
Method for leaching nickel, cobalt and manganese from waste lithium battery by using deep eutectic solvent
CN113930618A
Method for preparing electrocatalyst by efficiently recovering nickel, cobalt and manganese from waste lithium battery
CN116315230A
Method for recycling and regenerating positive electrode material of waste lithium ion battery by using deep eutectic solvent
CN117276731A
Method for preparing ternary precursor by recycling waste ternary lithium battery
CN118206161A
Cited By
Method for preparing high-purity manganese sulfate from low-grade rhodochrosite based on acetic acid and oxalic acid circulation
CN119706947A
A method for preparing high-purity manganese sulfate from low-grade rhodochrosite based on acetic acid and oxalic acid cycle
CN119706947B